Incidence of Canine Dilated Cardiomyopathy Diagnosed at Referral Institutes and Grain-Free Pet Food Store Sales: A Retrospective Survey - Quest, Bradley W.; Leach, Stacey B.; Garimella, Shiva; Konie, August; Clark, Stephanie D. (Frontiers in Animal Science, 2022)
Dilated cardiomyopathy (DCM) is considered a predominantly inherited disease in dogs. Recent reports suggest an increased incidence of DCM in atypical breeds eating grain-free and/or legume-rich diets. Emerging communications have noted that there is an apparent increase in the DCM incidence rate in the United States (US). However, little data regarding the incidence of DCM are currently available. To address the gap in the literature, this project examines the DCM incidence rate, over time, by retrospective polling of veterinary cardiologists across the US. Further, grain-free brick-and-mortar pet food market share data from 2011 to 2019 were presented. Fourteen US hospitals, out of 88 that were contacted to participate, provided all cardiology canine cases and of those, which specifically were diagnosed as DCM cases, for as many years as were available (1–20 years, average 8.1 years). This included a total of 68,297 canine patients evaluated by a cardiologist. Of the hospitals that participated, three provided age and breed data. A Poisson regression analysis revealed a statistically significant positive trend in the Mixed Breed group (P = 0.025, RC = 0.082), indicating that this group of dogs had an increased trend of DCM diagnoses over the past 15 years. However, there was no correlation (P = 0.16) for the Mixed Breed group and grain-free pet food sales data. The average incidence rate of DCM, amongst referral cases seen in the participating hospitals, was 3.90% (range 2.53–5.65%), while grain-free diet sales increased from 2011 to 2019. Nationally, the data did not support a significant change in percent DCM over time, from 2000 to 2019. There was no significant correlation between the national DCM incidence rate or the individual breed groups (P>0.05) in relation to the grain-free pet food sales. However, additional studies are necessary to understand whether regional factors contribute to increased DCM incidence rates within smaller cohorts.